Honesty Still Is the Best Policy. (September 2014) - Agassi, Joseph
Fuller describes the place of intellectuals in the modern world—as researchers, teachers, academics, and citizens. Their job is that of developing and promoting ideas. He explains their failure to perform well and offers advice: say what you think you should say, not necessarily what you think. The advice is unsuitable; it is aimed at advisers and expert witnesses, not at intellectuals. Also, his analysis invites proposals for social reforms aimed at lowering traditional expectations of intellectuals and toward presenting them with clearer and fairer job descriptions instead.